METHOD FOR MANUFACTURING RESIN FRAME-ATTACHED ELECTROLYTE MEMBRANE-ELECTRODE STRUCTURE FOR FUEL CELL - TANAKA YUKITO; MITSUDA NAOKI (2016)
PROBLEM TO BE SOLVED: To provide a method for manufacturing a resin frame-attached electrolyte membrane-electrode structure for a fuel cell, which makes possible to reliably remove gas from an adhesive layer even with a simple structure, and to make a high-quality firm bond between an electrolyte membrane-electrode structure and a resin frame member.SOLUTION: A method for manufacturing a resin frame-attached electrolyte membrane-electrode structure 10 comprises the steps of: forming an inclined adhesion face 26bs(r) by bending or curving an adhesion face 26bs of an inwardly-swelling part 24a of a resin frame member 24; disposing an adhesive 28a between the inclined adhesion face 26bs(r) and a solid polymer electrolyte membrane 18; and uniting a stepped MEA 10a and the resin frame member 24 into one by heating the adhesive 28a while keeping the inclined adhesion face 26bs(r) and the solid polymer electrolyte membrane 18 in parallel.SELECTED DRAWING: Figure 5 【課題】簡単な構成で、接着剤層からの空気抜きを確実に行うことができ、電解質膜・電極構造体と樹脂枠部材とを強固且つ高品質に接合することを可能にする。【解決手段】樹脂枠付き電解質膜・電極構造体１０の製造方法では、樹脂枠部材２４の内側膨出部２４ａの接着面２６ｂｓを屈曲乃至湾曲させて傾斜接着面２６ｂｓ（ｒ）が形成される。傾斜接着面２６ｂｓ（ｒ）と固体高分子電解質膜１８との間には、接着剤２８ａが配置される。そして、傾斜接着面２６ｂｓ（ｒ）と固体高分子電解質膜１８とを、平行状態に維持しながら接着剤２８ａを加熱することにより、段差ＭＥＡ１０ａと樹脂枠部材２４とが一体化される。【選択図】図５